Mechanisms of iron regulation of luminescence in Vibrio fischeri. - Haygood, M G (1985)
Synthesis of luciferase (an autoinducible enzyme) is repressed by iron in the symbiotic bioluminescent bacterium Vibrio fischeri. Possible mechanisms of iron regulation of luciferase synthesis were tested with V. fischeri and with Escherichia coli clones containing plasmids carrying V. fischeri luminescence genes. Experiments were conducted in complete medium with and without the synthetic iron chelator ethylenediamine-di(o-hydroxyphenyl acetic acid). Comparison of the effect of ethylenediamine-di(o-hydroxyphenyl acetic acid) and another growth inhibitor, (2-n-heptyl-4-hydroxyquinoline-N-oxide), showed that iron repression is not due to inhibition of growth. A quantitative bioassay for autoinducer was developed with E. coli HB101 containing pJE411, a plasmid carrying V. fischeri luminescence genes with a transcriptional fusion between luxI and E. coli lacZ. Bioassay experiments showed no effect of iron on either autoinducer activity or production (before induction) or transcription of the lux operon. Ethylenediamine-di(o-hydroxyphenyl acetic acid) did not affect luciferase induction in E. coli strains with wild-type iron assimilation (ED8654) or impaired iron assimilation (RW193) bearing pJE202 (a plasmid with functional V. fischeri lux genes), suggesting that the genes responsible for the iron effect are missing or substituted in these clones. Two models are consistent with the data: (i) iron represses autoinducer transport, and (ii) iron acts through an autoinduction-independent regulatory system (e.g., an iron repressor).